STUDY KELAYAKAN TAMBAK IKAN BANDENG DI DESA LAKUAN KABUPATEN BUOL SULAWESI TENGAH - Daimalindu, Ayu Septina (UNIVERSITAS NEGERI MAKASSAR, 2019)
ABSTRACTThis study aims to determine the feasibility of milkfish ponds in the village of Lakuan. The data sources used are primary data and secondary data. Primary data is data obtained directly from the field and the results of laboratory analysis while secondary data is data obtained from the Meteorology and Climatology Agency of Sultan Bantilan, Toli-Toli Regency. The method used in this study was purposive sampling. Based on the 6 sampling points determined based on the size and distance of the pond from the sea, the results obtained were temperatures ranging from 29,8 – 31,5ºC, dissolved oxygen ranged from 4 to 9,3 mg/l, the pH of the water ranged from 7,1 to 15, salinity ranges from 15,2 - 25 ppt, brightness ranges from 55,5% - 73%, ammonia ranges from 0,003 – 0,010 mg/l, phosphate from undetectable up to 0,018 ppt, soil texture between sandy clay - clay, soil pH ranges from 4,2 – 5,4, organic matter ranges from 3,78 – 4,78%, slope of 2%, mangroves are completely absent, seed availability is lacking, tides are 2,44 m, rainfall 1989,4 mm/year, the dry month amounts to 2 months, the river border is ± 1,000 m, the construction of the pond is in good condition and quite good, the depth ranges from 43 – 78,5 cm and the accessibility is sufficient. After analyzing the data using scoring, the results of this study indicate that the condition of milkfish ponds is in two categories, which are feasible and less feasible.